Upaya Hakim Pengadilan Agama Jember Menekan Angka Perceraian Melalui Mediasi dan Peluang Keterlibatan Tokoh Pesantren Tahun 2013: The Efforts of Judges at the Jember Religious Court to Reduce Divorce Rates Through Mediation and the Potential Involvement of Islamic Boarding School Leaders in 2013 - Muhammad Faisol (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2014)
Before addressing civil disputes in court, the first step a judge should take is to attempt mediation between the conflicting parties. Divorce cases in the Jember region are notably high. To make mediation more effective, the Jember Religious Court can involve community figures, especially those from Islamic boarding schools. The role of a kiai (Islamic boarding school leader) extends beyond being an educator; they also serve as a confidant for the community during conflicts, including family issues. This research aims to explore the efforts of judges at the Jember Religious Court to reduce divorce rates through court mediation by involving Islamic boarding school leaders. Sebelum menyelesaikan masalah perdata di pengadilan, langkah pertama yang harus dilakukan hakim adalah mencoba memediasi kedua pihak yang bersengketa. Kasus perceraian di wilayah Jember tergolong tinggi. Untuk membuat mediasi lebih efektif, Pengadilan Agama Jember sebenarnya dapat melibatkan tokoh masyarakat, terutama dari kalangan pesantren. Peran seorang kiai pesantren tidak hanya sebagai pendidik, tetapi juga sebagai tempat masyarakat mencurahkan perasaan saat terjadi konflik, termasuk masalah keluarga. Penelitian ini bertujuan untuk memahami upaya hakim Pengadilan Agama Jember dalam menekan angka perceraian melalui mediasi di pengadilan dengan melibatkan tokoh pesantren.